2021
DOI: 10.3390/genes12010073
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Exosomal RNAs in the Development, Diagnosis, and Treatment of Gastric Cancer

Abstract: Gastric cancer (GC) is one of the most common malignancies in the world. Exosomes, a subset of extracellular vesicles with an average diameter of 100 nm, contain and transfer a variety of functional macromolecules such as proteins, lipids, and nucleic acids. A large number of studies indicated that exosomes can play a significant role in the initiation and development of GC via facilitating intercellular communication between gastric cancer cells and microenvironment. Exosomal RNAs, one of the key functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…A recent study suggested that TDEs carrying programmed cell death 1 ligand 1 (PD-L1) retain immunosuppressive activity by downregulating T-cell surface CD69. 142 Recent research has shown that EVs produced by tumor cells also exhibit significant PD-L1 (Programmed Death Ligand) expression levels. PD-L1 greatly influences immunosuppression and immunotherapy resistance on EVs, which can attach directly to PD-1 on T cells.…”
Section: Sources Of Extracellular Vesiclesmentioning
confidence: 99%
“…A recent study suggested that TDEs carrying programmed cell death 1 ligand 1 (PD-L1) retain immunosuppressive activity by downregulating T-cell surface CD69. 142 Recent research has shown that EVs produced by tumor cells also exhibit significant PD-L1 (Programmed Death Ligand) expression levels. PD-L1 greatly influences immunosuppression and immunotherapy resistance on EVs, which can attach directly to PD-1 on T cells.…”
Section: Sources Of Extracellular Vesiclesmentioning
confidence: 99%
“…PDAC-derived sEVs contain different forms of RNAs, including micro RNAs (miRNAs), messenger RNAs (mRNAs), long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs). [54,55] RNAs in sEVs have been extensively studied, due to their critical roles in regulating almost all aspects of cancer-related metabolism and function. [56] Among these RNAs, miRNAs are the most studied target for cancer diagnosis/prognosis, whereas other RNAs may also act as potential biomarkers for PDAC diagnosis/prognosis.…”
Section: Rnasmentioning
confidence: 99%
“…Meanwhile, circRNAs are specific biomarkers for certain cancers [120]. The relationship between exosomal circRNA and tumor diagnosis was mainly concentrated in the diagnosis of lung cancer and breast cancer [121]. Zhu et al determined that the presence of hsa-circ-0013958 in the plasma of lung cancer patients was positively correlated with tumor metastasis, and it could be used as a biomarker for functional diagnosis and prognosis of lung cancer [122].…”
Section: Nucleic Acidsmentioning
confidence: 99%